Environmental aesthetics: A synthetic review. Issue 2 (5th May 2020) - Brady, Emily; Prior, Jonathan
Abstract: The main aim of the article is to provide up‐to‐date knowledge of environmental aesthetics for an interdisciplinary audience, and to signal the importance of research in this area for studying people–nature relationships. Environmental aesthetics has emerged in the last 50 years from the philosophical fields of aesthetics and environmental philosophy. Other disciplinary perspectives have also shaped environmental aesthetics, including landscape architecture, human geography, restoration ecology and empirical studies on landscape preferences in developmental and environmental psychology. This review and synthesis mainly addresses the theoretical approaches and concepts that provide a framework to the key debates in the field, but also considers how empirical approaches have shaped recent developments, and how conceptual issues arise with respect to empirical cases. We outline the background and context of environmental aesthetics, its key concepts, and provide a critical review of contemporary theories in the field. We then consider how aesthetics features in issues pertaining to the conservation, preservation, and restoration of nature. Finally, we identify some new directions for environmental aesthetics scholarship that can productively contribute to ongoing debates regarding various relationships between people and nature. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.